Liquid Disintegration Regime of Plain Orifice, Swirl, and Effervescent Atomization: A Review - Abdul Ghaffar, Zulkifli; Kasolang, Salmiah; Abdul Hamid, Ahmad Hussein; Reitz, Rolf D. (International Journal of Integrated Engineering, 2025)
Liquid atomization is a process in which bulk liquid disintegrates into sprays. Numerous liquid atomization mechanism theories have been developed to describe the disintegration process. The disintegration process of bulk liquid into sprays can be characterized using the liquid disintegration regime map. This map illustrates stages of liquid disintegration for a liquid atomization mechanism and is a helpful tool in understanding the underlying physics of a specific liquid atomization regime. However, a liquid disintegration regime map for a type of atomization, namely swirl effervescent atomization, is hardly available and is hypothesized in this paper. Swirl effervescent atomization has broad advantages within the hybrid category, and it is crucial to map the liquid disintegration regime for this type of liquid atomization. The first stage towards mapping the liquid disintegration regime is to review the liquid disintegration mechanisms. This article reviews the liquid disintegration regime of the plain orifice, swirl, and effervescent atomization considering their relation to swirl effervescent atomization.